2021
DOI: 10.3390/ijms22189956
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Dependent Antiapoptotic Effects of Cannabidiol for Keratinocytes Observed upon UV Irradiation

Abstract: Although apoptosis of keratinocytes has been relatively well studied, there is a lack of information comparing potentially proapoptotic treatments for healthy and diseased skin cells. Psoriasis is a chronic autoimmune-mediated skin disease manifested by patches of hyperproliferative keratinocytes that do not undergo apoptosis. UVB phototherapy is commonly used to treat psoriasis, although this has undesirable side effects, and is often combined with anti-inflammatory compounds. The aim of this study was to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…CBD does not change the percentage of cells undergoing apoptosis, even though it decreases the expression of caspases 3, 8, and 9 in the case of keratinocytes otherwise untreated. These results confirm the previously observed protective properties of cannabidiol [ 56 ]. However, a stronger inhibition of caspase expression is observed in the case of celecoxib-treated cells in which cannabidiol also decreases the number of cells undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…CBD does not change the percentage of cells undergoing apoptosis, even though it decreases the expression of caspases 3, 8, and 9 in the case of keratinocytes otherwise untreated. These results confirm the previously observed protective properties of cannabidiol [ 56 ]. However, a stronger inhibition of caspase expression is observed in the case of celecoxib-treated cells in which cannabidiol also decreases the number of cells undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…However, the study in Wistar rats indicated CBD (5 mg/kg)-induced PI3K/AKT and MAPK/ERK pathways associated with reducing reperfusion myocardial damage [ 86 ]. Moreover, CBD (4 μM) has been shown to reduce the p38 level in keratinocytes in the skin of healthy and psoriatic people [ 87 ]. It may therefore be suggested that changes in CBD-mediated AKT, as well as MAPK signaling, may play an important role in determining the cellular response to regulate intracellular homeostasis in pathological conditions by modulating Nrf2 transcription.…”
Section: The Modulatory Activity Of Cannabidiol With Respect To the N...mentioning
confidence: 99%
“…For instance, in vitro studies using 2D- and 3D-cultured skin cell models showed that CBD protects human skin keratinocyte cells from UV irradiation by alleviating cellular oxidative stress [ 2 ]. In addition, CBD reduces ultraviolet B (UVB)-induced apoptotic pathways by modulating cell death-related proteins such as pro-apoptotic prostaglandin, p-p38, and caspase-8 [ 3 ]. CBD has also been reported to restore redox balance by mediating UVB-induced lipid peroxidation products [ 4 ].…”
Section: Introductionmentioning
confidence: 99%